Christmas Witness Pursuit - Harris, Lisa, 1969- (New York, NY : Love Inspired, 2019)
Texas Ranger Alex Markham lands an unusual assignment-- protecting an ambassadors daughter on the African savanna. No one--not even wildlife filmmaker Meghan Jordan herself--can know his true identity. The stubborn but beautiful Meghan is nothing like the bookish woman he expected and neither is his unguarded reaction to her. For the cowboy-turned-cop, the routine babysitting assignment turns into a lifesaving mission when poachers target the unspecting beauty. But when Meghan learns the truth of Alexs identity, can she forgive him before their chances for a future are destroyed forever?
"Inspirational romantic suspense"--Spine.
Keywords: Texas Rangers -- Fiction; Fiction; Fiction; Man-woman relationships -- Fiction; Romantic suspense fiction; Romance fiction; Christian fiction